2017
DOI: 10.4038/tar.v28i3.8231
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on major chemical constituents in volatile oil of true cinnamon (<i>Cinnamomum verum</i> Presl. syn. <i>C. zeylanicum</i> Blum.) and five wild cinnamon species grown in Sri Lanka

Abstract: The genus Cinnamomum has 250 species distributed from South, East and South East Asia to Australia. There are eight species of cinnamon grown in Sri Lanka, of which, Cinnamomum verum Pres1 (syn. C. zeylanicum Blume) which is widely cultivated in the country. In addition, seven other species of wild cinnamon are also grown which are endemic to Sri Lanka which are considered wild cinnamon. In this study, six Cinnamomum species were selected namely Cinnamomum verum, Cinnamomum dubium Nees (Sinhala: Sewel Kurundu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…The results of the chemical analysis of the C. verum leaf EO agree with the findings of previous studies, which indicate that eugenol is its most abundant chemical component (77.22%) whereas the other chemical compounds appear in smaller concentrations. (40) The high occurrence and mortality rates associated with Candidiasis emphasise the urgent necessity for the introduction of new therapeutic approaches to treat candidiasis. Various studies conducted by multiple research groups has provided important knowledge about the pathogenesis of candidiasis, (15,41) and this knowledge should represent a starting point for the transformation of their findings into treatment strategies that can directly benefit patients suffering from Candida and other infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the chemical analysis of the C. verum leaf EO agree with the findings of previous studies, which indicate that eugenol is its most abundant chemical component (77.22%) whereas the other chemical compounds appear in smaller concentrations. (40) The high occurrence and mortality rates associated with Candidiasis emphasise the urgent necessity for the introduction of new therapeutic approaches to treat candidiasis. Various studies conducted by multiple research groups has provided important knowledge about the pathogenesis of candidiasis, (15,41) and this knowledge should represent a starting point for the transformation of their findings into treatment strategies that can directly benefit patients suffering from Candida and other infections.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the chemical analysis of the C. verum leaf EO agree with the findings of previous studies, which indicate that eugenol is its most abundant chemical component (77.22%) whereas the other chemical compounds appear in smaller concentrations. 40 …”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity of the extract was 345.2 µM Fe +2 /g dry mass using FRAP (ferric reducing antioxidant power) assay and with an IC50 value of 38.5 µg/mL using DPPH (1,1-diphenyl-2-picrylhydrazyl) assay. Liyanage et al [22] revealed that the highest percentage of volatile component (3.23%) was found in Cinnamomum verum leaf oil. Cinnamomum sinharajense recorded the highest bark oil content (3.53%), while Cinnamomum rivulorum recorded the lowest stem bark oil (0.51%) and leaf oil (0.41%) contents.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…General information: The true cinnamon ( C. zeylanicum , C. verum Lauraceae), also known as Ceylon cinnamon, is a plant originating from India and Sri Lanka, where it is used as a spice and in traditional medicine to treat different human diseases [ 76 ]. Cinnamon spice is obtained from different parts of the plants, such as the trunk bark, root, leaves, and flowers [ 77 ].…”
Section: Bioactive Compounds From Eos Of Spice Plantsmentioning
confidence: 99%